Polyphenolic profile and antioxidant and antibacterial activities of monofloral honeys produced by Meliponini in the Brazilian semiarid region. (June 2016) - Sousa, Janaína Maria; de Souza, Evandro Leite; Marques, Gilmardes; Meireles, Bruno; de Magalhães Cordeiro, Ângela Tribuzy; Gullón, Beatriz; Pintado, Maria Manuela; Magnani, Marciane
Abstract: This study assessed the polyphenolic profile and the antioxidant and antibacterial activities of monofloral honeys produced by Meliponini in the Brazilian semiarid region. Honeys from Ziziphus joazeiro Mart. (juazeiro) and Croton heliotropiifolius Kunth (velame branco) showed the highest total phenolic contents (TPCs) and the greatest antioxidant activity in assays with DPPH and ABTS + radicals. Honeys from Mimosa quadrivalvis L. (malícia) presented the strongest anti-peroxyl activity in ORAC assay. Juazeiro honeys showed the highest quantities of trans -cinnamic, p -coumaric, ellagic and ferulic acids, as well as of catechin, rutin, hesperetin and chrysin when compared to the other honeys produced by the same bee species. Malícia honeys showed the greatest quantities of myricetin, quercetin and kaempferol among the studied honeys. Honeys with the highest TPCs presented the highest antimicrobial activity. The results showed the impact of the floral source on the polyphenolic profile as well as on the antioxidant and antimicrobial properties of Meliponini honeys. Graphical abstract: Highlights: Ziziphus joazeiro honeys presented the highest quantities of phenolic acids. M. quadrivalvis honeys presented the strongest anti-peroxyl radical activity. Z. joazeiro and C. heliotropiifolius honeys showed high antibacterial activities.